2007
DOI: 10.1002/app.26476
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrical characterization of electrospun polyacrylonitrile‐derived carbon nanofibers

Abstract: Carbon nanofibers were produced from a polyacrylonitrile/N,N-dimethylformamide precursor solution by an electrospinning process and later pyrolysis at temperatures ranging from 500 to 11008C in an N 2 atmosphere for about 1 h. The morphological structure of the nanofibers was studied with scanning electron microscopy. Scanning electron microscopy images of carbonized polyacrylonitrile nanofibers without a gold coating showed that the carbonized polyacrylonitrile nanofibers possessed electrical properties. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 11 publications
(10 reference statements)
1
27
0
Order By: Relevance
“…However, the CVD method is complicated and costly procedure and is unable to produce the long fibers (9). Alternatively, carbon nanofibers (CNFs) can also be produced by pyrolyzing electrospun nanofibers from polymeric precursors mainly PAN (9,3,10). The PAN precursor nanofibers are converted to carbon counterparts by thermal treatments, including stabilization and carbonization (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, the CVD method is complicated and costly procedure and is unable to produce the long fibers (9). Alternatively, carbon nanofibers (CNFs) can also be produced by pyrolyzing electrospun nanofibers from polymeric precursors mainly PAN (9,3,10). The PAN precursor nanofibers are converted to carbon counterparts by thermal treatments, including stabilization and carbonization (3).…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylonitrile (PAN), whose behaviour in electrospinning is well known [30,[38][39][40][41], was used in the experiments. Electrospun PAN fibres have many possible applications, one of which is the production of carbon nanofibres (CNF) by carbonization of electrospun precursor fibres [17,21,25,26,29,[40][41][42][43][44][45]. CNTs can be used in precursor fibres since CNT filler may effectively resist heat shrinkage in composite fibres during the carbonization process [29].…”
mentioning
confidence: 99%
“…5). Agend et al (2007) fabricated carbon nanofibers by electrospinning of PAN from DMF solution and subsequent carbonization and found that average diameter of PAN nanofibers decreased from 149 to 109 nm by carbonization at 1100 °C. It should be emphasized in Fig.…”
Section: Uniaxially Aligned Carbon Nanofibers By Thermal Conversion Omentioning
confidence: 99%